Breast milk fatty acid composition has a long‐term effect on the risk of asthma, eczema, and sensitization. Issue 11 (26th August 2015) - van Elten, T. M.; van Rossem, L.; Wijga, A. H.; Brunekreef, B.; de Jongste, J. C.; Koppelman, G. H.; Smit, H. A.
Abstract Background Levels of n‐3 polyunsaturated fatty acids (PUFAs) and n‐6 PUFAs in breast milk are associated with the development of allergic diseases up to school age. However, it is unknown whether this relationship persists when the child becomes older. We therefore studied the association between levels of n‐3 PUFAs and n‐6 PUFAs in breast milk of allergic‐ and nonallergic mothers and asthma, eczema and sensitization up to the age of 14 years. Methods The study was nested in the ongoing PIAMA birth cohort. At the child's age of 3 months, 276 mothers provided a breast milk sample. Asthma (N total = 269) and eczema (N total = 274) were self‐reported up to the child's age of 14 years. Specific serum IgE levels were measured at the ages of 4, 8 and 12 years (N total = 216). Generalized estimating equations analyses were used to take account of repeated observations. Results Asthma up to the age of 14 years is less prevalent in children of allergic mothers receiving breast milk with higher levels of n‐3 long chain polyunsaturated (LCP) fatty acids (OR 0.50; 95% CI 0.31–0.79), and more prevalent in children of nonallergic mothers receiving breast milk with higher levels of n‐6LCP (OR 1.86; 95% CI 1.14–3.03). Weaker associations in similar direction were observed for eczema and sensitization. Direction of associations were consistent and of similar magnitude throughout childhood. Conclusion The association between breast milk fatty acid composition and asthma, eczema and sensitization persists up to the age of 14 years in children of both allergic and nonallergic mothers.